Recent Synthetic Strategies to Access Seven-Membered Carbocycles in Natural Product Synthesis - Nguyen, Thanh Vinh; Hartmann, Jan Marc; Enders, Dieter (Synthesis, 2013)
This methodology-oriented review covers the synthetic strategies to construct seven-membered carbocycles in naturally occurring compounds over the last ten years. It offers an insight into the common synthetic targets and approaches and provides useful information for further developments within this area of natural product synthesis as well as synthetic methodology in general. 1 Introduction2 Cyclization Reactions3 Cycloaddition Reactions3.1 [5+2] Cycloaddition3.2 [4+3] Cycloaddition3.3 Diels–Alder Reactions3.4 [2+2+2] Cycloaddition4 Ring-Closing Metathesis4.1 Ene–Ene Metathesis4.2 Ene–Yne Metathesis5 Ring-Expansion and Ring-Contraction Reactions5.1 Ring-Expansion Reactions5.2 Ring-Contraction Reactions6 Fragmentation and Isomerization Reactions7 Other Frequently Targeted Natural Products8 Conclusion
Keywords: seven-membered carbocycles; natural products; total synthesis; synthetic strategy; medium-sized carbocycles